2012
DOI: 10.1089/aid.2011.0073
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Production of Cytokines by T Cells Associates with the Activation/Exhaustion Status of Memory T Cells in Chronic HIV Type 1 Infection

Abstract: Chronic HIV-1 infection is characterized by immune cell dysfunctions driven by chronic immune activation. Plasma HIV-1 viral load (VL) is closely correlated with disease progression and the level of immune activation. However, the mechanism by which the persistent presence of HIV-1 damages immune cells is still not fully understood. To evaluate how HIV-1 affects disruption of T cell-mediated immune responses during chronic HIV-1 infection we determined the functional profiles of T cells from subjects with chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In contrast, enhancement of these pathways may be beneficial for the treatment of C. albicans infection. The IL-23/IL-17 axis is also thought to contribute to immunity against HIV; therefore, stimulation of these pathways may also be of particular benefit to patients coinfected with HIV and C. albicans (38)(39)(40). HIV infects and kills IL-17-secreting CD4 + T cells, but Vd1 T cells are expanded in patients with HIV infection (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, enhancement of these pathways may be beneficial for the treatment of C. albicans infection. The IL-23/IL-17 axis is also thought to contribute to immunity against HIV; therefore, stimulation of these pathways may also be of particular benefit to patients coinfected with HIV and C. albicans (38)(39)(40). HIV infects and kills IL-17-secreting CD4 + T cells, but Vd1 T cells are expanded in patients with HIV infection (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…3,35 The imbalanced production of cytokines by T cells is associated with the activation and exhaustive status of memory T cells in HIV-infected patients. 36 Here, we assessed the production of IL-17 and IFN-c by cd T cells in HIV-infected (Figure 6a). We found that the frequency of IL-17-producing cd T cells was increased in the ACUTE and SP groups and significantly increased in the FP groups, compared with the healthy controls (Figure 6b).…”
Section: Chronic Immune Activation Depletes Memory Vd 2 CD T Cells Inmentioning
confidence: 99%
“…This IFNγ+ bias is particularly clear in the response to long-circulating influenza strains, whereas a new pandemic influenza strain induced a mixed influenza-specific response [24] including both IL-2+IFNγ- and IL-2+IFNγ+ cells (abbreviated 2+γ- and 2+γ+, respectively). Similarly, the 2-γ+ cytokine expression pattern may be due to a population of exhausted Th1 cells [26][28] such as those expressing PD-1 and Tim3 [29], [30].…”
Section: Introductionmentioning
confidence: 99%